Dietary Moringa oleifera Alters Periparturient Plasma and Milk Biochemical Indicators and Promotes Productive Performance in Goats - Afzal, Ali; Hussain, Tarique; Hameed, Amjad; Shahzad, Muhammad; Mazhar, Muhammad Usman; Yang, Guan (Frontiers in Veterinary Science, 2022)
The purpose of the current study was to explore the supplementing effects of Moringa oleifera leaf powder (MOLP) on plasma and milk biochemical indices and productive/reproductive performance of goats. A total of thirty healthy pregnant goats were randomly distributed (n = 10) into three experimental groups: control (M0) group (basal diet without MOLP), M2% group (basal diet + 2% MOLP), and M3.5% group (basal diet + 3.5% MOLP). The experiment started 2 months before parturition and continued till the first month of lactation. The plasma flavonoids were significantly increased in M3.5% group during the entire experiment whereas; the total phenolic contents were enhanced only during the lactation period depending on the supplementation percentage. The amount of vitamin C increased significantly in M2% and M3.5% groups as compared to the M0 group. Supplementation of MOLP improved the plasma total antioxidant capacity by declining malondialdehyde concentration and total oxidant status values. The activities of superoxide dismutase and peroxidase enzymes were modified in M2% and M3.5% supplemented groups throughout the experiment, while the catalase activity was significantly influenced only during the lactation stage. The protein and lycopene contents in plasma were significantly improved in M3.5% group, whereas the total sugars and carotenoid level was increased in both M2% and M3.5% groups. Dietary supplementation with 3.5% MOLP more effectively enhanced protease and amylase activities as compared to 2% supplementation. MOLP also improved the biochemical indices and antioxidant status of colostrum and milk. The milk yield, weight gain of the kids and reproductive performance was high in M2% and M3.5% groups in comparison to M0 group. These findings disclose that supplementing the diet with 3.5% MOLP improves antioxidant status, milk yield, and reproductive performance in goats.